2012
DOI: 10.21608/jacb.2012.54981
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Microbiological Evaluation of Some Fish Products Samples

Abstract: Different kinds of fish products namely canned, salted, smoked, and frozen fish were collected from local markets in Damietta Governorate. The aim of this study was to report if these fish products were in compatible with Egyptian standard specifications or not. Subsequently, be ensure that these fish products highly consumed in Damietta Governorate were safe foods for human or not. Total viable bacterial count, aerobic spore forming bacteria, Staphylococcus aureus, coliform group, Clostridium spp. and anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
4
4
0
Order By: Relevance
“…However, acidity percentages in frozen Mackerel varied from 1.75 ± 0.057% to 1.56 ± 0.033%. These results are consistent with the results recorded by El-Dengawy et al (2012).…”
Section: Resultssupporting
confidence: 94%
“…However, acidity percentages in frozen Mackerel varied from 1.75 ± 0.057% to 1.56 ± 0.033%. These results are consistent with the results recorded by El-Dengawy et al (2012).…”
Section: Resultssupporting
confidence: 94%
“…Results indicated that all samples were in acceptable boundary of processed mackerel (<40 mgN/100g) according to EOS (2005). In agreement with the results of El-Dengawy et al, (2012), all canned fish samples had low profile of TVB-N, which might be due to low counts of total viable bacterial count.…”
Section: Resultssupporting
confidence: 88%
“…In table (2) the result agrees with (El-Dengawy et al, 2012) who mentioned that the count of aerobic spore formers in 2 samples of frozen mackerel were 0.044±0.044x103and 1.30±0.760x103 cfu /gm respectively. Also, the results was agreed with (Mansour, 2001) who found that in one hundred and twenty random samples of smoked fish, salted sardines, canned salmon and canned tuna the total aerobic spore formers were ranged between 1x102 to 5x10 ,1x10 to 3x10 ,1x10 to 5x10 and 1x10 to 3x10 cfu/gm, respectively.…”
Section: Discussionsupporting
confidence: 88%